PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK, STORE ATMOSPHERE, DAN E-WOM TERHADAP PROSES KEPUTUSAN PEMBELIAN (SURVEI TERHADAP KONSUMEN ZENBU-HOUSE OF MOZARU PARIS VAN JAVA, BANDUNG) - Alvendo Teguh Santosa (Universitas Kristen Maranatha, 2019)
Bandung is a city in Indonesia with big tourism potential. Culinary tourism is one of the most iconic tourism themes in Bandung. One of the most demanded culinary is Japanese Fusion style food that Zenbu-House of Mozaru in Paris Van JavaMall (Zenbu PVJ). In order to increase consumer’s interest, management needs strategies are based from service quality, product quality, store atmosphere and e-WOM. This study uses non-probability sampling technique with purposive sampling method. Based on index assessment, respondents rate service quality, product quality, and store atmosphere good rating whereas e-WOM is rated with moderate assessment. Overall the purchasing decision process is rated with good assessment. This study uses multiple regression analysis, t-test, F-test, and the coefficient of determination analysis as the analysis tools. The result shows that service quality, product quality, store atmosphere, and e-WOM are simultaneously influenced the purchasing decision process of Zenbu PVJ. While partially, service quality, and e-WOM influence the purchasing decision process whereas product quality and store atmosphere do not influence the purchasing decision process. Keywords: E-WOM; Product Quality; Purchasing Decision Process; Service Quality; Store Atmosphere